Study of optical properties of (PMMA) doped by methyl red and methyl blue films - Abdul-Allah, Muhammad H. (Iraqi Journal of Physics, 2019)
The effect of doping by methyl red and methyl blue on the absorption spectra and the optical energy gap of poly (methyl methacrylat) PMMA film have been studied. The optical transmission (T%) in the wavelength range 190-900 nm for films deposited by using solvent casting method were measured. The Absorptance data reveals that the doping affected the absorption edge as a red and blue shift in its values. The films show indirect allowed interband transitions that influenced by the doping. Optical constants; refractive index, extinction coefficient and real and imaginary part of dielectric constant were calculated and correlated with doping.